The influence of polyelectrolytes architecture on calcium sulfate dihydrate growth retardation - Oner, M; Dogan, O; Oner, G (ELSEVIER SCIENCE BV, 1998)
The retarding influence of acidic acrylate and methacrylate polymers made by group transfer polymerization on the growth of calcium sulfate dihydrate was examined in aqueous solution. The variations with polyelectrolyte charge, structure and molecular weight have been tested. The inhibition increases with the acid content of the polymers. Acrylates were much more effective than equivalent methacrylates. The higher inhibition efficiency is related to the maximum surface charge density due to adsorbed polymer. (C) 1998 Elsevier Science B.V. All rights reserved.
Keywords: crystal growth; gypsum precipitation; acrylic polyelectrolyte; habit modification; CRYSTAL-GROWTH; POLY-ELECTROLYTES; BARIUM-SULFATE; ADDITIVES; ADSORPTION; GYPSUM; PRECIPITATION; INHIBITION; Crystallography; Materials Science; Physics